Does friction contribute to formability improvement using servo press? - Kali Prasad; Aishwary Gupta; Hariharan Krishnaswamy; Uday Chakkingal; Dilip K. Banerjee; Myoung-Gyu Lee (Friction)
Abstract Servo press forming machines are advanced forming systems that are capable of imparting interrupted punch motion, resulting in enhanced room temperature formability. The exact mechanism of the formability improvement is not yet established. The contribution of interrupted motion in the ductility improvement has been studied through stress relaxation phenomena in uniaxial tensile (UT) tests. However, the reason for improved formability observed when employing servo press is complicated due to the additional contribution from frictional effects. In the present work, an attempt is made to decouple the friction effect on formability improvement numerically. The improved formability is studied using a hole expansion test (HET). The limit of forming during hole expansion is modeled using the Hosford-Coulomb (HC) damage criteria, which is implemented as a user subroutine in a commercial explicit finite element (FE) software. Only the contribution of stress relaxation is accounted for in the evolution of the damage variable during interrupted loading. Therefore, the difference between simulation and experimental hole expansion ratio (HER) can be used to decouple the friction effect from the overall formability improvement during hole expansion. The improvement in HER due to stress relaxation and friction effect is different. The study showed that the model effectively captures the hole expansion deformation process in both monotonic and interrupted loading conditions. Compared to stress relaxation, friction effect played a major role during interrupted HET.